2005
DOI: 10.1088/0022-3727/38/8/026
|View full text |Cite
|
Sign up to set email alerts
|

Database system of thermodynamic properties of individual substances at high temperatures

Abstract: Theoretical starting points and methods leading to the creation of a consistent database of thermodynamic properties of individual substances are given. The database is easy to modify and update. An exact definition of the concept consistent is given after all the relations and connections have been given. The proposed general methods are realized using computer programs and the species file, in which the thermodynamic properties of 326 gaseous and 34 condensed substances are stored that were prepared from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…First we calculated the plasma composition of air at 20 kK and 1 bar, according to [16] with species standard thermodynamic functions taken over from [17]. The spectral absorption coefficient was then calculated with the approach given by Aubrecht et al [18] and is shown in Fig.…”
Section: More Realistic Spectrummentioning
confidence: 99%
“…First we calculated the plasma composition of air at 20 kK and 1 bar, according to [16] with species standard thermodynamic functions taken over from [17]. The spectral absorption coefficient was then calculated with the approach given by Aubrecht et al [18] and is shown in Fig.…”
Section: More Realistic Spectrummentioning
confidence: 99%
“…In the mixture of SF 6 and Cu plasma, we assume the following species: SF 6 molecules, S, F, Cu neutral atoms, S + , S +2 , S +3 , F + , F +2 , Cu + ions and free electrons. Molecular products of SF 6 dissociation were neglected due to the lack of data for their absorption coefficients.…”
Section: Absorption Properties Of Plasmamentioning
confidence: 99%
“…We have only taken into account SF 6 molecules with their experimentally measured absorption cross sections [5]. The equilibrium composition of the plasma was taken from [6]. In Fig.…”
Section: Absorption Properties Of Plasmamentioning
confidence: 99%
See 2 more Smart Citations